Performance analysis of satellite-terrestrial integrated wireless network based on stochastic geometry - LI Ruiwen; SUN Yaohua; PENG Mugen (Dianxin kexue)
Satellite-terrestrial integrated wireless network (STIN) is a pivotal approach in achieving worldwide wireless connectivity. To guide base stations deployment of STIN, an analysis of the uplink coverage probability was conducted. Stochastic geometry was used to modeled the STIN under a setting of distinct frequencies. The satellite stations modeled as a one-dimensional Poisson point process (PPP) on orbit, base stations and users were represented as two-dimensional PPP. The expression for the uplink coverage probability was derived in terms of parameters such as base station density and orbital inclination. The correctness of the derived expression was verified through experimental simulations, and the impact of network parameters on the uplink coverage probability were analyzed.